HIV Infection, Vascular Disease, and Stroke - Chow, Felicia C. (Seminars in Neurology, 2014)
With the transformation of HIV infection into a chronic disease for the majority of patients with access to combination antiretroviral therapy, HIV-infected individuals and their medical providers are facing a new set of challenges, many of which are more typical of an aging population. Accumulating evidence indicates that rates of stroke, like coronary heart disease, may be higher in HIV-infected individuals. This review will discuss the epidemiology of stroke in HIV infection, potential mechanisms underlying the pathogenesis of stroke, vascular risk and cognitive impairment, cardiovascular and stroke risk prediction, and strategies for stroke prevention in this at-risk population, with a focus on HIV-associated cerebrovascular disease in the current era of highly effective combination antiretroviral therapy
Keywords: human immunodeficiency virus infection; stroke; ischemic stroke; cerebrovascular disease; cardiovascular risk; intracerebral hemorrhage